2019
DOI: 10.14202/vetworld.2019.1491-1498
|View full text |Cite
|
Sign up to set email alerts
|

Immune-inflammatory concept of the pathogenesis of chronic heart failure in dogs with dilated cardiomyopathy

Abstract: Background: Dilated cardiomyopathy is common in dogs. This form of cardiomyopathy is the main cause of death due to heart disease in dogs. Death can occur suddenly in clinically normal animals as a result of the progression of congestive heart failure (CHF). The pathogenesis of heart failure syndrome in dogs with dilated cardiomyopathy involves activation of the neurohumoral system and immune-mediated inflammation, which leads to further progression of the condition. Heart failure syndrome in dogs with dilated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
(79 reference statements)
0
11
0
3
Order By: Relevance
“…Although both of them are commonly considered non-inflammatory conditions [ 6 , 7 ], studies have found increased circulating inflammatory cytokines in dogs and humans with CHF due to MMVD [ 8 , 9 ] and DCM [ 7 , 10 ]. Increased expression and release of inflammatory cytokines such as tumour necrosis factor (TNF-α), as well as serum C-reactive protein (CRP), have been described in humans [ 11 , 12 ] and dogs with CHF [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although both of them are commonly considered non-inflammatory conditions [ 6 , 7 ], studies have found increased circulating inflammatory cytokines in dogs and humans with CHF due to MMVD [ 8 , 9 ] and DCM [ 7 , 10 ]. Increased expression and release of inflammatory cytokines such as tumour necrosis factor (TNF-α), as well as serum C-reactive protein (CRP), have been described in humans [ 11 , 12 ] and dogs with CHF [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary and acquired pathologies in animals of both non-infectious and contagious etiology are very diverse and complex, characterized by various forms of manifestations, which are often difficult to diagnose and require special approaches in treatment and prevention [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Endocardiosis in dogs is characterized by chronic myxomatous degeneration of the mitral valve, which leads to thickening and incomplete closure of its cusps and the development of mitral regurgitation whose severity is the main determinant of disease progression. It should be noted that most dogs with endocardiosis have an asymptomatic course for many years or even throughout their lives [4,9,10]. However, with progressive mitral regurgitation, severe complications can arise in the form of development of left-sided and then rightsided congestive chronic heart failure (CHF), usually secondary to the high pulmonary arterial hypertension syndrome [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although both of them are commonly considered non-in ammatory conditions (6,7), studies have found increased circulating in ammatory cytokines in dogs and humans with CHF due to MMVD (8,9) and DCM (7,10). Increased expression and release of in ammatory cytokines such as tumour necrosis factor (TNF-α), as well as serum C-reactive protein (CRP), have been described in humans (11,12) and dogs with CHF (13).…”
Section: Introductionmentioning
confidence: 99%